Strategies for Internationalizing the Renminbi - Cao, Yuanzheng (Research Series on the Chinese Dream and China's Development Path,, 2018)
This book presents the theoretical framework for the evolution of the international monetary system and the internationalization of the RMB. Combining theoretical research and empirical study, it then provides an in-depth analysis of the relevant issues from multiple perspectives based on this framework. Written by former chief economist at the Bank of China, this book explains the "two-step strategy" from the capital account opening to the full convertibility of the RMB, it also analyzes the status and functions of the HK offshore financial market in internationalizing the RMB.